آبی ذرائع کا عسکری استعمال: تجزیاتی مطالعہ: Military Use of Water Resources: Analytical Study (Al-Qamar, 2021)
This article intends to describe the military usage of water resources in historical perspective. In this regard, the evidence, and instances of military usage of water resources have been described from the Quran, Hadith, and Islamic history. Moreover, some examples from the world history also testify that military use of water was also common in almost all the regions and nations of the world. These sources candidly reflect that the history of military usage of water is almost as old as man himself. Today, the scarcity of water has become a bone of contention among nations, and this is considered the major cause of modern wars too. Furthermore, it will devise the different tactics of the usage of water resources. On the one hand it can be defensive to protect the army or castles, on the other hand it can be aggressive to attack on rival troops. This article will describe the rulings of Islamic law or sharia, containing specific guidelines regarding the use of water in military contexts. It will also tell the permissibility or unacceptability of these acts as well.
Keywords: Water sources; Military usage; Quran; Hadith; Islamic History